(Mebel Rumah Q-ta): Mebel Rumah Q-Ta - Widia; Ce Gunawan (CV ODIS, 2021)
This study aims to examine the effect of online marketing and service quality on purchasing decisions at furniture store Rumah Q-ta in Sukabum City. This research category is categorized as descriptive research using a quantitative approach. The population of this research is the consumer of furniture store Rumah Q-ta in Sukabumi City. The research sample was 100 respondents. Data collection using a questionnaire. Testing the quality of the instrument using validity and reliability tests. Further testing the fulfillment of classical assumptions and multiple linear regression analysis which includes the t statistical test and F statistical test. The result showed that partially and simultaneously online marketing and service quality had a positive and significant influence on purchasing decision variables. Consumers view the online marketing of furniture store Rumah Q-ta as very attractive and good, the service quality is under what consumers want.